Esophageal Intramural Pseudodiverticulosis and Esophagobronchial Fistula Palliated with Esophageal and Bronchial Stenting: A Rare Case Report. Issue 2 (June 2022) - Nitz, Jonathan A.; Mirza, Mohammed H.; Whorf, Daniel H.; Austin, Brett; Anderson, Richard C.
Esophageal intramural pseudodiverticulosis (EIP) is a rare condition characterized by outpouchings from the esophageal lumen into the outer esophageal wall. It can lead to complications such as esophageal strictures presenting as dysphagia and esophagobronchial fistula (EBF) presenting as recurrent aspiration pneumonia. Only 1 other report of EIP with EBF has been reported in the literature. EIP itself is typically managed medically while a complication such as EBF, on the other hand, elicits far more invasive approaches in the form of open surgical intervention. We present the case of a 50 year-old male newly diagnosed with EIP complicated by EBF who was palliated with esophageal stenting. Upper endoscopy with esophageal stent placement offers a safe, feasible, and non-operative therapy for EIP and EBF.